Uji Efektivitas Krim Anti-Aging Ekstrak Etanol Akar Pasak Bumi (Eurycoma longifolia Jack) pada Kulit Punggung Kelinci Albino yang Terpapar Sinar UV-A - Puspitasari, Ismi; Waty, Carolina Eka (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Eurycoma longifolia Jack (Tongkat Ali) root, rich in phenolic compounds with antioxidant and anti-aging properties, was formulated into an anti-aging cream. This study aimed to meet physical quality standards and evaluate in-vivo efficacy on rabbit dorsal skin exposed to UV-A radiation. The root extract, prepared through maceration, was formulated into creams at concentrations of 1.5%, 3%, and 6%, meeting physical quality criteria. Anti-aging effectiveness was assessed in five shaved rabbits exposed to 6 hours of daily UV-A radiation for 14 days. Each treated rabbit's dorsal skin, exposed to UV-A, was divided into five areas for cream application over 28 days: area I was applied with a negative control (ointment base), area II with a positive control, and areas III-V with a series concentrations of the extract cream of Eurycoma longifolia Jack. Anti-aging parameters, including collagen and elasticity percentages measured with a skin analyzer at pre-exposure (T0), after 14 days (T1), and after 28 days of cream application (T2). The result demonstrated that the 6% concentration yielded the most significant effects. The tested cream met high physical quality standards, showcasing potential as a promising anti-aging formulation.